Biomedical ethics - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
Explores medical ethics, system of moral principles that apply values and judgments to the practice of medicine.
Executive producer, Nasuhi Yurt.
Host : MaryLynn Schiavi.
DVD format.
Keywords: Medical ethics; Bioethics; Ethics, Medical